Effect of dietary supplementation with rocket salad (Eruca sativa) seeds powder on certain seminal plasma traits of Hy – line laying breeder roosters subjected to oxidative stress induced by hydrogen peroxide: Hazim J. Al – Daraji1 and R. H. Razuki2 - Al – Daraji, Hazim J. (The Iraqi Journal of Veterinary Medicine, 2012)
This study was conducted to evaluate the effect of adding different levels of rocket salad seeds powder to the diet on seminal plasma traits of roosters subjected to oxidative stress induced by hydrogen peroxide. A total of 60 Hy – line laying breeder roosters 57 weeks old were used in this study. Roosters were randomly distributed into 5 treatments with 3 replicates each. Each replicate constituted of 4 roosters (12 roosters for each treatment). Experimental treatments were as following: T1: Males fed control diet and normal water, T2: Males fed diet supplemented with 3 gm rocket salad powder / kg of diet + 0.25 ml hydrogen peroxide (0.5%) / litter of water, T3: Males fed diet supplemented with 3 gm rocket salad powder / kg of diet + 0.5 ml hydrogen peroxide (0.5%) / litter of water, T4: Males fed diet supplemented with 3 gm rocket salad powder / kg of diet + 1 ml hydrogen peroxide (0.5%) / litter of water, and T5: Males fed control diet and drink tap water supplemented with 1 ml hydrogen peroxide (0.5%) / litter of water. Males were treated with hydrogen peroxide (6%) and rocket salad for 12 weeks starting from 59 week of male ages. Results revealed that treated the roosters with hydrogen peroxide without adding rocket salad powder to the diet of these roosters (T5) resulted in highly significant (p< 0.01) decrease as regards concentrations of phospholipids, cholesterol, glutathione, the activity of superoxide desmutase and catalase, and total antioxidant activity in seminal plasma and highly significant (p< 0.01) increase concerning concentrations of tyrosine and malondialdehyde as compared with control group (T1) and rocket salad powder treatments (T2, T3, T4) after 12 weeks of experiment. However, supplementing diet of roosters with rocket salad powder (T2, T3, T4) resulted in highly significant (p< 0.01) increase with relation to concentrations of phospholipids, cholesterol, glutathione, the activity of superoxide desmutase and catalase, and total antioxidant activity in seminal plasma and highly significant (p< 0.01) decrease respecting concentrations of tyrosine and malondialdehyde as compared with (T5) In conclusion adding rocket salad powder to the diet of roosters had important role in limiting the negative effect of oxidative stress induced by hydrogen peroxide on seminal plasma quality of roosters. Therefore, dietary supplementation with rocket salad powder could be used as one of important tools for improving semen quality of roosters.